The relationship between dietary intake of ω-3 and ω-6 fatty acids and frailty risk in middle-aged and elderly individuals: a cross-sectional study from NHANES - Yan, Zhaoqi; Xu, Yifeng; Li, Keke; Zhang, Wenqiang; Liu, Liangji (Frontiers in Nutrition, 2024)
Background: Frailty is a complex clinical syndrome characterized by a decline in the functioning of multiple body systems and reduced adaptability to external stressors. Dietary ω-3 fatty acids are considered beneficial dietary nutrients for preventing frailty due to their anti-inflammatory and immune-regulating properties. However, previous research has yielded conflicting results, and the association between ω-6 fatty acids, the ω-6: ω-3 ratio, and frailty remains unclear. This study aims to explore the relationship between these factors using the National Health and Nutrition Examination Survey (NHANES) database. Materials and Methods: Specialized weighted complex survey design analysis software was employed to analyze data from the 2005-2014 NHANES, which included 12,315 participants. Multivariate logistic regression models and restricted cubic splines (RCS) were utilized to assess the relationship between omega intake and frailty risk in all participants. Additionally, a nomogram model for predicting frailty risk was developed based on risk factors. The reliability of the clinical model was determined by the area under the receiver operating characteristic (ROC) curve, calibration curves, and decision curve analysis (DCA). Results: In dietary ω-3 intake, compared to the T1 group (≤1.175 g/d), the T3 group's intake level (>2.050 g/d) was associated with approximately 17% reduction in frailty risk in model 3, after rigorous covariate adjustments (odds ratio (OR) = 0.83, 95% confidence interval (CI): (0.70, 0.99)). In dietary ω-6 intake, the T2 group's intake level (>11.423, ≤19.160 g/d) was associated with a 14% reduction in frailty risk compared to the T1 group (≤11.423 g/d) (OR: 0.86, 95% CI: 0.75, 1.00, P = 0.044). RCS results indicated a non-linear association between ω-3 and ω-6 intake and frailty risk. Both ROC and DCA curves demonstrated the stability of the constructed model and the effectiveness of an omega-rich diet in reducing frailty risk. However, we did not find a significant association between the ω-6: ω-3 ratio and frailty.This study provides support for the notion that a high intake of ω-3 and a moderate intake of ω-6 may contribute to reducing frailty risk in middle-aged and elderly individuals.